2020
DOI: 10.3389/fpls.2020.590968
|View full text |Cite
|
Sign up to set email alerts
|

Phytonutritional Content and Aroma Profile Changes During Postharvest Storage of Edible Flowers

Abstract: Edible flowers are niche horticultural products, routinely used as cooking ingredients in the food industry. Currently, new species are required with the aim of enlarging the number of species with a long shelf-life, healthy nutraceutical compounds, and new fragrance and tastes. Ageratum houstonianum Mill, Tagetes lemmonii A. Gray, Salvia dorisiana Standl, and Pelargonium odoratissimum (L.) L’Hér “Lemon” were selected for their different morphological characteristics and color. Fresh flowers were analyzed to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 99 publications
4
12
0
Order By: Relevance
“…A relatively low number of compounds have been detected in extracts obtained from the floral tissues of P. 'Endsleigh' flowers; we have identified approximately the same number of flavonoids as Boukhris et al [28] in leaves and flowers of P. graveolens, but far fewer than the 40 compounds found by Marchioni et al [29] in Pelargonium odoratissimum 'Lemon' or of over 50 compounds identified in the flowers of P. endliclerianum [30]. Few metabolites are in common with the flower of Geranium sylvaticum [22] but those shared kaempferol, quercetin and myricetin methyl ethers, are known to function as defensive compounds against herbivorous insects [31].…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…A relatively low number of compounds have been detected in extracts obtained from the floral tissues of P. 'Endsleigh' flowers; we have identified approximately the same number of flavonoids as Boukhris et al [28] in leaves and flowers of P. graveolens, but far fewer than the 40 compounds found by Marchioni et al [29] in Pelargonium odoratissimum 'Lemon' or of over 50 compounds identified in the flowers of P. endliclerianum [30]. Few metabolites are in common with the flower of Geranium sylvaticum [22] but those shared kaempferol, quercetin and myricetin methyl ethers, are known to function as defensive compounds against herbivorous insects [31].…”
Section: Discussionsupporting
confidence: 72%
“…The level of total phenolic compounds was significant; the reported values are similar to those of flowers of P. odoratissimum [29] in which TPC content was the highest among the flowers of the four species analysed, and approximately 40% and 50% higher than that one of the flowers of Geranium sylvaticum [32] and P. graveolens flowers [28], respectively. Comparing with literature regarding edible flowers, the TPC content results 50% higher than the best of the 26 flowers analysed by Demasi et al [33] and within the range of values reported by Janarny et al [34] for Sri Lankan edible flowers.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Principal component analysis (PCA) and hierarchical cluster analysis (HCA) were performed as reported in a previous study [43]. Briefly, a matrix of correlation was used for the measure of eigenvalues and eigenvectors in PCA analysis where the plot was performed selecting the two highest principal components (PCs).…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, cold storage is a common nontoxic treatment for prolonging the shelf life of flowers. This treatment first affects the visual quality of flowers, and hydration is an important feature in maintaining the shape of flowers once they are bloomed Marchioni et al (2020). investigated the cold storage of four edible flowers (Ageratum houstonianum, Tagetes lemmonii, Salvia dorisiana, and Pelargonium odoratissimum) for 0-6 days.…”
mentioning
confidence: 99%